APLIKASI SISTEM INFORMASI AKUNTANSI PEMBELIAN KREDIT (STUDI KASUS : PT BERSAMA CIPTA RASA MULYA) - Tri Ramdhany; Rio Andriyat Krisdiawan (Cloud Information, 2018)
Purchasing is the most important thing in a business process company. Every business activity must make the purchase process, whether it is engaged in services, buying and selling, or industry. Similarly, what happens in PT Bersama Cipta Rasa Mulya, a company engaged in the sale of bread always makes purchases of credit on raw materials needed for production activities. The process of recording credit purchase transactions and repayment of credit purchases is still done on a page by page so there is often a delay in making the report. Therefore, tools are needed to make reporting easier and more automated. This raw material purchase application can manage the recording, ordering, purchasing, returning purchase, recording of credit purchase repayment, and reporting on supplier assessment. The methodology chosen to build tools in the form of this application is a prototype methodology that is adapted with the needs of authors in data collection. While the tools used in system design analysis is Flow map, Context Diagram, Data Flow Diagram, Data Dictionary, and Entity Relationship Diagram. Implementation of system design uses Visual Basic for Applications by using Microsoft Access 2013 as a database. This application can facilitate in recording transactions and making reports relating to the purchase of raw material credit and facilitate in making supplier selection decisions before making purchases of credit transactions of raw materials. Keywords: Credit Purchase, Raw Material, Supplier Rating, Database, Prototype